State Regulation of Community Paramedicine Programs: A National Analysis. (4th March 2018) - Glenn, Melody; Zoph, Olivia; Weidenaar, Kim; Barraza, Leila; Greco, Warren; Jenkins, Kylie; Paode, Pooja; Fisher, Jonathan
Abstract: Background : Community Paramedicine (CP) is a rapidly evolving field within prehospital care where paramedics step outside of their traditional roles of treating acute conditions to provide elements of primary and preventive care. It is unclear if current state oversight regarding the scope of practice (SOP) for paramedics provides clear guidance on the novel functions provided and skills performed by CP programs. Objective : To determine the process and authority, as currently defined by state laws and regulations in the United States, to expand paramedic SOP in order to perform CP roles and to assess state EMS agencies' interpretation of paramedic SOP as it applies to CP. Methods : We conducted a systematic review of laws, regulations, and policies from the 50 U.S. states in effect between February and June 2016 that define or apply to paramedic SOP. We determined whether each state's SOP included 21 potential skills applicable to CP within the following categories: assessment, treatment & intervention, referrals, and prevention & public health. Laws were also queried for mechanisms for expanding SOP, alternate destinations, and community paramedicine for each state. Additionally, we surveyed representatives from U.S. State Emergency Medical Services (EMS) agencies and asked which of these skills were a part of their current SOP. All data was coded into Excel™ and analyzed using descriptive statistics. Results : All 50 U.S. states have laws relating to EMS. Forty-one states have a statewide SOP (82%), and 3 states have statewide protocols from which the SOP has been inferred for purposed of this study, but may not legally constitute SOP in this jurisdiction (6%). 20 states (40%) had a clearly defined mechanism for expanding SOP. Sixteen states (32%) had laws specific to CP. Seven states (14%) allowed for patients to be transported to alternate destinations. Of the 21 skills surveyed, on average there were 8.63 (6.41–10.85) fewer skills for paramedics found in state SOP laws and regulations than were reported as being a part of a state's paramedic SOP . All skills demonstrated variability between the legal review and survey results with 13.04–96.15% concordance. Conclusion : There is a lack of guidance and consistency regarding CP programs and scope of practice. Further studies are needed to understand best practices around regulation and oversight of CP.